Graphitic C3N4 quantum dots for next-generation QLED displays. (January 2019) - He, Liangrui; Fei, Mi; Chen, Jie; Tian, Yunfei; Jiang, Yang; Huang, Yang; Xu, Kai; Hu, Juntao; Zhao, Zhi; Zhang, Qiuhong; Ni, Haiyong; Chen, Lei
Graphical abstract: Abstract: Quantum dot light-emitting diode (QLED) displays are considered a next-generation technology, but previously reported quantum dots (QDs) consisting of heavy metals are toxic and harmful. This work examined earth-abundant, metal-free, graphitic C3 N4 (g-C3 N4 ) with exceptional optical and electronic properties, excellent chemical and thermal stability, an appropriate band gap, and non-toxicity for QLED applications. The dependence of the luminescence performance on the reaction atmosphere and temperature; the transformation of the crystal and electronic structures during the reaction, including crystal defects and surface functional groups; and the luminescence mechanisms of g-C3 N4 were uncovered. The highest quantum yield of 49.8% was achieved by the sample possessing the highest graphitic-to-triazine carbon ratio synthesized at 500 °C under N2 atmosphere. The disappearance of the charge-transfer band, crystal defects (traps), and non-radiative transition (due to fast relaxation) from the absorption spectra demonstrates the enhanced quantum efficiency of the g-C3 N4 QDs over that of the bulk powders. A QLED prototype device employing g-C3 N4 QDs as the blue-emitting layer was demonstrated.